1987
DOI: 10.1002/dc.2840030303
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cytology: Six years of experience

Abstract: This article deals with a 6-yr mass screening program for the early detection of endometrial cancer, which took place 1978-1983. The diagnostic accuracy of endometrial cytology and the possibility of integrating this technique with the hysteroscopy and endometrial biopsy were studied. The authors analyzed 2,504 outpatients, all over the age of 45. The results of endometrial cytology were compared with those found using hysteroscopy and endometrial biopsy. Endometrial cytology showed high sensitivity in diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The new plastic brush "endocyte" sampling device provides a fast and simple method of obtaining specimens of good quality in about 80% of cases, with minimum trauma for the patient (Ferenczy and Gelfand, 1984). Despite this improvement, cytodiagnosis from these specimens lacks accuracy, especially in differentiating dysfunctional pathology of the endometrium, particularly hyperplastic lesions (Ferenczy and Gelfand, 1984;Mencaglia, 1987;Kashimura et al, 1988). This has raised the question whether the use of MAbs, identifying well-characterized TAA, may improve the current performance of endometrial cytodiagnosis, allowing more accurate screening of symptomatic and highrisk asymptomatic post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The new plastic brush "endocyte" sampling device provides a fast and simple method of obtaining specimens of good quality in about 80% of cases, with minimum trauma for the patient (Ferenczy and Gelfand, 1984). Despite this improvement, cytodiagnosis from these specimens lacks accuracy, especially in differentiating dysfunctional pathology of the endometrium, particularly hyperplastic lesions (Ferenczy and Gelfand, 1984;Mencaglia, 1987;Kashimura et al, 1988). This has raised the question whether the use of MAbs, identifying well-characterized TAA, may improve the current performance of endometrial cytodiagnosis, allowing more accurate screening of symptomatic and highrisk asymptomatic post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be due to the well-known influence that hormonal status, previous diagnostic procedures and intrauterine contraceptive devices (Kashimura et al, 1988) may have on the endometrial morphology. Furthermore, about 50% of the patients with ongoing uterine bleeding have no detectable pathological lesions of the endometrium, and thus require more extensive diagnostic procedures (Mencaglia, 1987). The results of this immunocytochemical testing have shown that MAbs AR-3 and B72.3, although not able to discriminate between hyperplasia and endometrial carcinoma, may represent a useful adjunct to endometrial cytology complementing conventional morphology in (1) identifying those endometrial atypical hyperplastic lesions which have been epidemiologically identified as precursors of carcinoma (Kurman and Norris, 1982;Kurman et al, 1985;Ferenczy and Gelfand, 1989), and (2) defining, on the basis of the antigenic phenotype, the malignant nature of those endometrial lesions with uncertain cytological aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Одной из главных задач совре-менной онкогинекологии является изучение раз-личных аспектов патогенеза предраковых процес-сов [12] и рака шейки матки [10]. Клетки диффуз-ной эндокринной системы участвуют в физиологи-ческих процессах, которые протекают циклически в матке: овариально-менструальный цикл у женщин и эстральный цикл у животных [2,7].…”
Section: експериментальна медицина і морфологіяunclassified